Comparative Study of Different Methods For Improvement of Power System Stability - et al., Prof. P.M. Mankar (International Journal of Advanced Science and Technology, 2019)
Power system stability plays an important role in power system problems. There are various problems occurs in power system because of instability. The main focus of this paper is related with the stability studies of the power system . There are various parameters which hammers stability of power system like rotor instability , voltage instability , frequency instability etc. So it  is necessary  to improve stability of power system for reliable and secure operation. There are  different techniques like classical and advanced  to improve the stability of power system. In this paper we have focused on improvement of voltage stability using classical and advanced techniques. And hence by giving comparative analysis of these methods conclusion is drawn.